Successful renal transplant in a patient with non‐Herlitz junctional epidermolysis bullosa. (April 2014) - Ungureanu, S.; Adni, T.; Brown, T.; Inston, N.; Heagerty, A.
Summary Non‐Herlitz junctional epidermolysis bullosa (NH‐JEB) is a very rare inherited disorder, with an array of complications. We present the case of a 33‐year‐old patient of Chinese origin, diagnosed with NH‐JEB in childhood, who developed severe IgA nephropathy. His renal impairment was initially treated by haemodialysis. He underwent successful renal transplantation, resulting in normalization of his renal function. To our knowledge, this is the first report of renal transplantation in a patient with epidermolysis bullosa, which should support use of this intervention in other similar cases.